Lime, gypsum, and nitrogen as drivers to increase the abundance of soil fungi and N-cycling microorganisms in integrated agricultural systems - Barcelos, Jéssica P.Q. [UNESP]; Sánchez-Rodríguez, Antonio Rafael; Bargiela, Rafael; Mariano, Eduardo [UNESP]; Gloyshina, Olga V.; Jones, Davey L.; Rosolem, Ciro A. [UNESP] (Elsevier, 2024)
Soil microbial communities are drivers of carbon (C) and nitrogen (N) cycling in terrestrial ecosystems and provide early indicators of how management affects soil quality. Microbial community structure and function are affected by soil pH and N fertilization and may be affected by lime and gypsum, but there is a gap in the knowledge on the interaction with N, particularly in integrated systems. We evaluated the short-term effects of superficial lime and gypsum application along with N-fertilizer on soil properties and microbial communities, via phospholipid fatty acid profiling and Illumina 16S ribosomal RNA amplicon sequencing. Soil pH proved to be the most important characteristic regulating soil microbial structure in this tropical oxisol. In the absence of N fertilization, lime and gypsum alleviated acidity stress, decreased the Gram-positive to Gram-negative bacterial ratio (−8 %), and increased the fungal-to-bacterial ratio (+38 %). In addition, arbuscular mycorrhizal fungi (AMF) were enhanced (+36 %). Lime and lime+gypsum favored the relative abundance of important taxonomic groups involved in the N cycle. N-fertilizer application also increased the relative abundance of groups involved in N cycling, except for bacterial genera involved in N2 fixation. We conclude that alleviation of acid stress by the application of lime ± gypsum increased the relative abundance of beneficial microbial groups (i.e. AMF, Gram- and N cycling bacteria) resulting in shifts in microbial community composition, potentially promoting both C and N cycling.
Keywords: Microbial diversity; N-cycling microorganisms; no-tillage; prokaryotic communities; soil acidity; soil conservation